Access to education inspectorate in Spain. A Delphi technique study - Rodríguez Bravo, Marcos Francisco; Camacho Prats, Alexandre; Álvarez Álvarez, Carmen (Avances en Supervisión Educativa, 2019)
The Educational Inspection in Spain is a service of the Educational Administration with main functions to ensure compliance with the laws and contribute to the improvement of quality and equity in education. Making an adequate selection of education inspectors is, therefore, key so that they can perform these important functions. In Spain, access to the Inspectorate is carried out through competitive examination, regulated by Royal Decree 276/2007. However, the norm allows access to teachers without having passed the opposition and there are no formative requirements in education sciences; in addition, both reference authors and the supervising professional groups themselves consider that the Inspection is in crisis. For this reason, we have implemented an study based on the Delphi technique with 20 specialists, both Education inspectors and academic University experts in Supervision to know their impressions about the current access to the Inspectorate and what should be the best way, in order to select the best candidates in the best possible way. The results obtained show that some aspects are relevant, but it is suggested to modify others, reaching agreements on the access requirements, the updating of the agenda, the evaluation of the managerial, teaching and research experience, include a psychological test, among others. We may conclude that access to the Educational Inspection in Spain should be modified in different levels in order to improve the institution itself and general education with it.
Keywords: education inspectorate; school inspector; inspector recruitment; recruitment process; access to inspectorate; delphi technique